ROLE OF 64-SLICE MULTI DETECTOR COMPUTED TOMOGRAPHY FOR NON-INVASIVE VISUALISATION OF CORONARY ARTERY BYPASS GRAFTS FOR FOLLOW UP IN POST CABG PATIENTS - Naveed, Tahir; Ayub, Muhammad; Nazeer, Mohsin; Mallick, Nadeem Hayat; Mohydin, Bilal S.; Ali, Zulfiqar (Journal of Ayub Medical College Abbottabad, 2010)
Background: Coronary artery bypass graft surgery is a commonly performed revascularization procedure in ischemic heart disease patients. Conventional coronary angiography is an invasive method for evaluation of grafts in such patients. Non-invasive evaluation of grafts in post CABG patient has been made possible with the advent of 64-Slice Multi Detector Computed Tomography (MDCT) .The Objective of the study was to non-invasively assess the graft patency with MDCT. Methods: Sixty post CABG patients (52 male, 8 female) with atypical chest pain or stable angina were evaluated with MDCT for graft patency. The grafts were considered as patent if there was continuous lumen visualisation at origin, in the body and at its insertion with native recipient vessels. Grafts were defined as blocked when only stumps were seen. They were classified as stenotic if there was ‰¥50% diameter narrowing. Results: The mean age of the patients was 60.1±9.7 years, mean duration since CABG was 8.01±6 years. Total number of grafts assessed was 175 including 124 (71%) venous grafts and 51 (28.9%) arterial grafts. A total of 82/124 (66.1%) venous grafts and 47/51 (92%) arterial grafts were patent. Forty-two (34%) venous grafts were blocked whereas 4 arterial grafts were not developed. Arterial grafts patency was 92% and venous grafts patency was 67.7% after a mean follow up of 8.01±6 years. Conclusion: The study shows that 64 slice MDCT can be used for the evaluation of patency and occlusion of venous and arterial grafts in post CABG patients for follow up. Keywords: Multi Detector Computed Tomography (MDCT), Coronary Artery Bypass Graft (CABG), Graft Patency (GP)